2009
DOI: 10.1017/s0263034609000020
|View full text |Cite
|
Sign up to set email alerts
|

Three–dimensional simulations of a solid graphite target for high intensity fast extracted uranium beams for the Super–FRS

Abstract: This paper presents three-dimensional numerical simulations of thermodynamic and hydrodynamic response of a wheel shaped solid graphite production target for the super conducting fragment separator (Super-FRS) that is irradiated with a fast extracted high intensity uranium beam. These fragment separator experiments will be carried out at the future Facility for Antiprotons and Ion Research (FAIR), at Darmstadt. Previously, we reported simulation results that were carried out using two-dimensional computer code… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
(15 reference statements)
0
11
0
Order By: Relevance
“…Currently the scientific community shows great interest in warm dense matter phenomena, which are studied with intense laser and particle beams. Most of this work does address basic physics issues of matter under extreme conditions Ni, et al, 2008;Piriz et al, 2002Piriz et al, , 2003aPiriz et al, , 2003bPiriz et al, , 2005Piriz et al, , 2006Piriz et al, , 2008Tahir et al, 1999Tahir et al, , 2000aTahir et al, , 2000bTahir et al, , 2001aTahir et al, , 2001bTahir et al, , 2003Tahir et al, , 2004Tahir et al, , 2005bTahir et al, , 2005cTahir et al, , 2006Tahir et al, , 2007aTahir et al, , 2007bTahir et al, , 2008bTahir et al, , 2009aTahir et al, , 2009bTemporal et al, 2003Temporal et al, , 2005 or is related to inertial fusion physics (Bangerter et al, 1982;Deutsch, 1986;Logan et al, 2008;Long & Tahir, 1982, 1986, 1987Piriz & Wouchuk, 1992;Tahir & Long, 1982, 1983, 1984. …”
Section: Hydrodynamic Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently the scientific community shows great interest in warm dense matter phenomena, which are studied with intense laser and particle beams. Most of this work does address basic physics issues of matter under extreme conditions Ni, et al, 2008;Piriz et al, 2002Piriz et al, , 2003aPiriz et al, , 2003bPiriz et al, , 2005Piriz et al, , 2006Piriz et al, , 2008Tahir et al, 1999Tahir et al, , 2000aTahir et al, , 2000bTahir et al, , 2001aTahir et al, , 2001bTahir et al, , 2003Tahir et al, , 2004Tahir et al, , 2005bTahir et al, , 2005cTahir et al, , 2006Tahir et al, , 2007aTahir et al, , 2007bTahir et al, , 2008bTahir et al, , 2009aTahir et al, , 2009bTemporal et al, 2003Temporal et al, , 2005 or is related to inertial fusion physics (Bangerter et al, 1982;Deutsch, 1986;Logan et al, 2008;Long & Tahir, 1982, 1986, 1987Piriz & Wouchuk, 1992;Tahir & Long, 1982, 1983, 1984. …”
Section: Hydrodynamic Simulation Resultsmentioning
confidence: 99%
“…Due to its robustness, carbon is very widely used in construction of the production targets for generating radioactive beams (Tahir et al, 2005a(Tahir et al, , 2008a(Tahir et al, , 2008b(Tahir et al, , 2009a.…”
Section: Introductionmentioning
confidence: 99%
“…However, such target concept has never been employed in practice for very high intensity fast extracted beams like those at the Super-FRS. Extensive theoretical work has been carried out over the past years [38][39][40][41][42][43] to design a viable solid graphite production target for the Super-FRS. Substantial progress has been made in this respect as summarized below.…”
Section: The Super-frs Production Targetmentioning
confidence: 99%
“…To find a solution to this problem, we have carried out extensive theoretical studies over the past years. A brief overview of this work is presented in this paper while the details can be found elsewhere [38]- [43].…”
Section: Introductionmentioning
confidence: 99%
“…Present results, however, have shown that due to three dimensional effects the maximum intensity that can be used with such a target is limited to 3 × 10(11) ions per spill [23], [24], [25], [26].…”
Section: Outreach Of High Energy Density Experiments Into Other Fieldmentioning
confidence: 99%